Control of chronic lymphocytic leukemia development by clonally-expanded CD8 + T-cells that undergo functional exhaustion in secondary lymphoid tissues - Hanna, Bola S.; Schmidt, Manfred; Gabriel, Richard; Lichter, Peter; Seiffert, Martina (Leukemia, 2019)
Chronic lymphocytic leukemia (CLL) is associated with substantial alterations in T-cell composition and function. However, the role of T-cells in CLL remains largely controversial. Here, we utilized the Eµ-TCL1 mouse model of CLL as well as blood and lymph node samples of CLL patients to investigate the existence of anti-tumoral immune responses in CLL, and to characterize involved immune cell populations. Thereby, we identified an oligoclonal CD8+ effector T-cell population that expands along with CLL progression and controls disease development. We further show that a higher percentage of CD8+ effector T-cells produces IFNγ, and demonstrate that neutralization of IFNγ results in faster CLL progression in mice. Phenotypical and functional analyses of expanded CD8+ effector T-cells show significant differences in disease-affected tissues in mice, with cells in secondary lymphoid organs harboring hallmarks of activation-induced T-cell exhaustion. Notably, we further describe a respective population of exhausted CD8+ T-cells that specifically accumulate in lymph nodes, but not in peripheral blood of CLL patients. Collectively, these data emphasize the non-redundant role of CD8+ T-cells in suppressing CLL progression and highlight their dysfunction that can be exploited as target of immunotherapy in this malignancy.
Published: 28 September 2018
Gesehen am 05.07.2019